Use of sequential lateral flow assays to diagnose cryptococcal infection among people living with HIV in Monrovia, Liberia - Barclay-Korboi, Yassah M.; Adeel, Alina; Ajami, Ibrahim; Dickson, Flinhway Hessou; Wachekwa, Ian; Vaye, Nyenyakar A. F.; Levitz, Stuart M. (PLoS neglected tropical diseases, 2025)
Cryptococcal meningitis is one of the top causes of morbidity and mortality in people living with HIV/AIDS. In high prevalence regions, current recommendations are to screen individuals with blood CD4 + T cell counts less than 200 cells/µl for serum cryptococcal antigen (CrAg) and then preemptively treat those who test positive for presumed cryptococcosis. However, in many low-resource settings, including Monrovia, Liberia, flow cytometric CD4 assays are not readily available. We tested subjects with known HIV infection using a lateral flow assay (LFA), which provides a semi-quantitative determination of whether the blood CD4 + T cell count is ≤200 cells/µl. Subjects with counts ≤200 cells/µl were then tested with an LFA that detects CrAg. Of the 500 HIV+ subjects tested, 201 (40.2%) had blood CD4 + T cell count ≤200. Of those, 82/201 (40.7%) were serum CrAg+. Subjects who were serum CrAg+ were more likely to have a Glasgow Coma Score <15, whereas subjects who were CrAg- were more likely to be HIV-2+. Lumbar punctures were performed on 61 serum CrAg+ subjects; 30/61 (49.2%) subjects were cerebrospinal fluid CrAg+. Thus, sequential point-of-care testing enabled the diagnosis of cryptococcosis in HIV+ individuals with blood CD4 T cell counts ≤200 cells/µl. As diagnostic testing informs life-saving therapies, it is imperative that these assays are made readily available in resource-poor settings.